Impact Of Traditional Market Development And Revitalization For Traders (Case Study At Sentul Traditional Market, Yogyakarta City) - Riko Romadon Indika; Heri Prasetyo (Penerbit Hellow Pustaka, 2024)
Traditional markets need to be improved, namely the physical structure of the market, cleanliness, dry floors that are not muddy, arrangement of sellers' locations according to the class of goods being sold. To find out the impact of development and revitalization of the Sentul traditional market. research includes research that uses qualitative analysis. The data sources used are primary data and secondary data. After all the data was collected, analysis was then carried out using qualitative descriptive methods. Based on the research results, it can be seen the impact of the development of traditional market revitalization for traders. The satisfaction of public facilities in the new market is felt by the presence of car parking and excalators to make it easier for customers to get to the places they want to visit.